Sulfur Hexafluoride (SF6) versus Perfluoropropane (C3F8) in the Intraoperative Management of Macular Holes: A Systematic Review and Meta-Analysis - Idan Hecht; Michael Mimouni; Eytan Z. Blumenthal; Yoreh Barak (Journal of Ophthalmology)
Purpose. A systematic literature search was conducted to identify and review studies comparing SF6 to C3F8 as a tamponade agent in the intraoperative management of macular holes. Methods. Publications up to October 2018 that focused on macular hole surgery in terms of primary closure, complications, and clinical outcomes were included. Forest plots were created using a weighted summary of proportion meta-analysis. Analysis was performed separately for SF6 and C3F8. A random effects model was used, and corresponding I2 heterogeneity estimates were calculated. Results. Nine pertinent publications studying a total of 4,715 patients were identified in 2000 to 2017, including two randomized studies (n=206), two prospective studies (n=170), and five retrospective or registry-based studies. Similar rates of closure between SF6 and C3F8 were reported in eight out of nine studies, regardless of subgroup analyses. All studies reporting visual outcomes showed similar results when comparing SF6 to C3F8 at one to six months of follow-up. Neither agent was clearly associated with increased risk of ocular hypertension, cataract formation, or other adverse events. Meta-analytic pooling of the closure rates in the SF6 group resulted in 91.73% (95% confidence interval: 88.40 to 94.55, I2: 38.03%), and for C3F8, the closure rate was 88.36% (95% confidence interval: 85.88 to 90.63, I2: 0.0%). Conclusions. Both SF6 and C3F8 appear to have achieved similar visual outcomes and primary closure rates and neither was associated with an increased risk of adverse events. Considering the more rapid visual recovery with SF6, there appears to be no evidence to support C3F8 as the tamponade agent of choice for macular hole surgery.